2016
DOI: 10.1177/0013916515614368
|View full text |Cite
|
Sign up to set email alerts
|

If You Build It Will They Come? Does Involving Community Groups in Playground Renovations Affect Park Utilization and Physical Activity?

Abstract: In a sample of racially, ethnically, and socioeconomically diverse neighborhoods, using a quasi-experimental, prospective, longitudinal study design, we examined whether involvement of community groups in playground design selection, installation, and ongoing maintenance influences park utilization and moderate-to-vigorous physical activity (MVPA) post-playground renovations (N = 78 matched parks, 39 intervention/39control). Parks were matched on size, proximity, neighborhood socioeconomic status, and race/eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 47 publications
3
48
1
1
Order By: Relevance
“…Although commonly studies evaluating effects of park refurbishments on physical activity and park use have been conducted alongside recreation programs (e.g., park-based physical activity programs) [ 33 , 35 ] or community engagement [ 36 ], few have studied the effects of park refurbishment alone [ 33 , 34 , 35 ]. Two of these studies involving park refurbishment alone were also set in lower socioeconomic areas of Melbourne.…”
Section: Discussionmentioning
confidence: 99%
“…Although commonly studies evaluating effects of park refurbishments on physical activity and park use have been conducted alongside recreation programs (e.g., park-based physical activity programs) [ 33 , 35 ] or community engagement [ 36 ], few have studied the effects of park refurbishment alone [ 33 , 34 , 35 ]. Two of these studies involving park refurbishment alone were also set in lower socioeconomic areas of Melbourne.…”
Section: Discussionmentioning
confidence: 99%
“…King et al (2015) demonstrated significant improvements in park usage (p = 0.004) and physical activity of users (p = 0.007) after the transformation of 2 acres of undeveloped green space into a recreational park (including footpaths, playing fields, benches and basketball courts) and a community garden in an area of transitional housing for the homeless and refugees. Slater et al (2016) showed significant improvements in park usage and physical activity levels of users over time (up to 12 months) in 39 intervention parks that undertook major improvements including replacement of old playground equipment and ground surfacing, coupled with extensive community engagement activities to encourage and promote park usage, compared with control sites.…”
Section: Park-based Interventionsmentioning
confidence: 99%
“…Еще в одном американском исследовании получен двукратный прирост количества посетителей (преимущественно детей и лиц среднего возраста) и их ФА после установки нового детского игрового оборудования, фитнес-тренажеров, увеличения площади озеленения, по сравнению с контрольными парками [36]. В другом исследовании отмечается, что хорошо спроектированная детская игровая площадка стимулирует посещать парк не только детей, но взрослых (как правило, родителей), а также повышает вероятность физически активного отдыха в парке [37].…”
Section: изменения инфраструктуры в проспективных исследованияхunclassified